2019
DOI: 10.3390/jpm9040051
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of MicroRNA Gene Polymorphisms in the Pathogenesis of Diabetes and Atherosclerotic Cardiovascular Disease

Abstract: MicroRNAs (miRNAs) are endogenous, small (18–23 nucleotides), non-coding RNA molecules. They regulate the posttranscriptional expression of their target genes. MiRNAs control vital physiological processes such as metabolism, development, differentiation, cell cycle and apoptosis. The control of the gene expression by miRNAs requires efficient binding between the miRNA and their target mRNAs. Genome-wide association studies (GWASs) have suggested the association of single-nucleotide polymorphisms (SNPs) with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 145 publications
(243 reference statements)
1
32
0
Order By: Relevance
“…These are released as paracrine factors by both living and dying cardiomyocytes and thus these may act as effective biomarkers in predicting heart attack. Several studies have investigated the association between miRNA gene variations and susceptibility to various diseases, such as diabetes, atherosclerosis and coronary artery disease [ 7 , 8 ]. Several recent studies reported association of the genetic variants with different metabolic diseases in different genes, including the seed region of the miRNAs [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are released as paracrine factors by both living and dying cardiomyocytes and thus these may act as effective biomarkers in predicting heart attack. Several studies have investigated the association between miRNA gene variations and susceptibility to various diseases, such as diabetes, atherosclerosis and coronary artery disease [ 7 , 8 ]. Several recent studies reported association of the genetic variants with different metabolic diseases in different genes, including the seed region of the miRNAs [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the association between miRNA gene variations and susceptibility to various diseases, such as diabetes, atherosclerosis and coronary artery disease [ 7 , 8 ]. Several recent studies reported association of the genetic variants with different metabolic diseases in different genes, including the seed region of the miRNAs [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Our earlier reports indicated the potential association of the miRNAs gene polymorphism with the risk of developing CAD, as well as its association with different cardiometabolic phenotypes to stratify the CAD burden in the general population [ 7 , 8 , 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A functional single nucleotide polymorphism of miR‐499 gene has been identified recently. The A/G polymorphism (rs3746444) is located in the stem region of the mature miR‐499 sequence as shown in Figure 1 (Elfaki et al, 2019; Hu et al, 2008; Toraih et al, 2017). According to the in silico characterization, the gene targets of A and G allele of miR‐499 differed significantly in their gene targets (Toraih et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(a) Structural prediction of the microRNA 499 (rs3746444). The site of single nucleotide polymorphisms (SNPs) (73 T>C), probably a stem‐loop SNP in the predicted microRNA structure, is indicated with arrow (adapted and modified from Elfaki et al., 2019). (b) Genomic structure of human miR‐499A gene with the chromosomal location along the long arm of chromosome 20q11.22.…”
Section: Introductionmentioning
confidence: 99%